Penyuluhan SOP Tes dan Pengukuran Kekuatan Otot Tungkai dan Pengukuran Panjang Tungkai - Hartanto; Achmad Furqon Bildhonny; Aang Ghunaifi Dardiri (CV. Multi Kreasi Media, 2025)
The counseling service Counseling on SOP Test and Measurement of Leg Muscle Strength and Leg Length Measurement adds knowledge to improve knowledge and improve physical fitness and maximize jumping during the match. In addition, athletes can raise awareness to maintain muscle and leg strength during the match. Partners in this service are UNHASA CUP volleyball players. The approach method used in solving problems is direct discussion with athletes, designing and preparing the tools and materials needed to conduct counseling on SOP tests. Data collection techniques using measurement tests and observations. The results obtained from this service are: 1) increased knowledge about counseling on SOP tests for measuring Leg Muscle Strength and Leg Length Measurement. Through this service, it was found that through counseling on Leg Muscle Strength Measurement and Leg Length Measurement in order to improve the knowledge and skills of athletes in increasing jumps during the match. The hope with the counseling activities related to SOP Tests and Measurements of leg muscles and leg length to athletes is that athletes not only know the theory of leg muscles and leg length and applicable test SOPs but also have skills in physical training in increasing jumps and understanding.